Taṭbīqu Wasīlaty Fīdiyō fīī at-Ta‘līm al-Lughah al-‘Arabiyyah ‘Alā Dāfi‘iyyah Talāmīdż bil-Madrasah al-Mutawassiṭhoh al-Islāmiyyah Maftāḥul Hudā Jenggawah - Fitriyah, Faizah; Huda, Mokhammad Miftakhul; Anam, Syamsul; Costley, Jamie; Yu, Jianfei (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study is motivated by the importance of using appropriate learning media to achieve learning objectives optimally, especially in Arabic language learning, which often faces challenges such as low student interest and motivation. One of the media that can be used is video, as it presents material in an audio-visual form, making it more engaging and easier to understand. This study aims to describe the implementation of video media in Arabic language learning in class VIII B at MTs Maftahul Huda Jenggawah. This research employs a qualitative approach with a field research (case study) design. Data collection techniques include observation, interviews, and documentation. Data analysis uses the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The validity of the data is ensured through source triangulation and technique triangulation. The results of the study show that the implementation of video media in Arabic language learning is carried out systematically through several stages: the teacher prepares the lesson plan (RPP), prepares multimedia equipment, opens the lesson, explains the learning objectives, delivers the material, uses video media that is appropriate and supports the material, provides additional explanations, concludes the lesson, and closes the learning session. The use of video media contributes positively to creating a more engaging and interactive learning environment. This study contributes to the development of Arabic language learning based on digital media and can serve as a reference for teachers in implementing innovative teaching strategies. Future research is recommended to examine the effectiveness of video media on students’ learning outcomes quantitatively or through experimental studies by comparing various types of learning media.